Learning Experience in the Mini Museum Atsiri Oil in Sarinah Jakarta Indonesia with the Application of Video Mapping Technology - Chintya Sagita Goestien; Dianing Ratri; Andriyanto Wibisono (Universitas Pendidikan Indonesia (UPI), 2023)
In the last two decades, museums have experienced rapid changes in the application of technology. Some museums use digital technology to stimulate visitor curiosity and present collections interestingly. Technological developments can be enjoyed by various age groups and become an opportunity to attract visitors, especially young people. The mini museum Atsiri Sarinah Jakarta presents the experience of plants with the application of digital technology, one of which is video mapping. Applying elements that visitors really like because they have aesthetic qualities that have a positive effect, namely plants. This is intended to make visitors more enthusiastic about exploring the museum space. The purpose of this research is to validate the extent to which visitors can learn information through experience, regarding the role of the museum space in educating essential oil products as Indonesian cultural heritage. The research was conducted using a mixed method exploratory sequential approach, qualitatively conducting interviews with Atsiri and quantitatively providing questionnaires to validate the learning experience of visitors. The results show the learning experience through digital installations such as video mapping makes visitors learn new and interesting things, understand all the information during the visit, and learn more about essential oil products.